2019
DOI: 10.1080/13880209.2019.1687526
|View full text |Cite
|
Sign up to set email alerts
|

Coix lachryma-jobi extract ameliorates inflammation and oxidative stress in a complete Freund’s adjuvant-induced rheumatoid arthritis model

Abstract: Context: Adlay seed [Job’s tears, Coix lachryma-jobi L. var. ma-yuen Stapf (Poaceae)] is a Traditional Chinese Medicine, which has been investigated to treat inflammatory diseases and rheumatism.Objective: This study evaluates the ameliorative effects of adlay seed extract (ASE) in a complete Freund’s adjuvant (CFA)-induced rheumatoid arthritis (RA) rats.Materials and methods: The RA Sprague–Dawley rat model was induced and randomly divided into six groups with or without ASE treatment (50, 100 or 200 mg/kg). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 38 publications
1
38
0
Order By: Relevance
“…2B), demonstrating that ICA could attenuate the iron deposit in LPS-induced synoviocytes. GPX, an antioxidant enzyme (35), was also detected in the present study. GPX levels were significantly reduced by LPS compared with the control group.…”
Section: Ica Attenuates Cell Death and Increases Cell Viability In Lpsupporting
confidence: 79%
“…2B), demonstrating that ICA could attenuate the iron deposit in LPS-induced synoviocytes. GPX, an antioxidant enzyme (35), was also detected in the present study. GPX levels were significantly reduced by LPS compared with the control group.…”
Section: Ica Attenuates Cell Death and Increases Cell Viability In Lpsupporting
confidence: 79%
“…Although there are many anti-RA drugs in clinic, such as immunosuppressants, biological agents, DMARDs, steroidal drugs, and NSAIDs, most of them are associated with long-term adverse effects and costs (Li et al, 2019b;Dai et al, 2020;Zhu et al, 2020). In addition, the CFA-induced arthritis (AIA) model and the collagen-induced arthritis model are two typical preclinical experimental animal models of RA, and the former is a classic, easy-to-measure, short duration, reliable and reproducible test animal model, which is extensively used for the preclinical evaluation of anti-RA drugs since its pathological and morphological characteristics were similar to those of human RA Pan et al, 2017;Voon et al, 2017;Zhang et al, 2019;Saleem et al, 2020). The roots of P. heterophyllum have been widely used to treat RA as a vital TCM for centuries (Editorial Committee of Traditional Chinese Medicine 1999;, but their anti-RA effect and chemical profiling have not been reported so far.…”
Section: Discussionmentioning
confidence: 99%
“…Hs-CRP and ESR were commonly used in the laboratory to diagnose the activity of rheumatic diseases, and can be used as indicators to monitor the activity of diseases and evaluate the treatment stability. Association rules show that compared with single use Chinese traditional medicine group, XFC combined traditional Chinese medicine on IL-11, IL-17, PD-L2, hs-CRP, anti-CCP have obvious correlation, showed that after the combined traditional Chinese medicine can significantly improve the indicators, and the mechanism may be related to the pharmacological effects of XFC, semen coicis extract exerts anti-RA effects via inhibiting pro-inflammatory factors and alleviating oxidative stress [28];The active components of radix astragali can strengthened humoral and cellular immunity and improved the regulation of human immunity [29].…”
Section: Analysis Of Association Rules Between the Improvement Of Patmentioning
confidence: 99%